EFL Students’ attitude towards Quizizz-Mediated Assessment tool in Reading Classroom - Irsyad, Muhammad Fadhilah; Miftakh, Fauzi; Ridwan, Iwan (Jurnal Ilmiah Wahana Pendidikan, 2024)
This study focused on investigate students’ attitude towards Quizizz in reading classroom. The participant took 4 students for being interviewed. The study used qualitative analysis to observe the data. The result showed students that they had positive responses to the Quizizz experience. The students indicated that they had positive attitude based on three components. In affective component, students revealed exhibit a high level of satisfaction and enthusiasm when using Quizizz in their reading classes. For behavioral, students are more willing to participate in class activities due to the interactive and enjoyable nature of Quizizz. Furthermore in cognitive Quizizz functions as a tool that aids students in understanding and engaging with the learning material more effectively